Knowledge Level of Clinical Dental Students in Faculty of Dentistry, Universitas Sumatera Utara Regarding the Anesthetic Technique of Inferior Alveolar Nerve Block : Tingkat Pengetahuan Mahasiswa Kepaniteraan Klinik Fkg Usu Mengenai Teknik Anestesi Blok Nervus Alveolaris Inferior Dan Penatalaksanaan Kegagalannya Pada Perawatan Gigi Mandibula (TALENTA, 2021)
The inferior alveolar nerve block technique (Fischer's method) is a local anesthetic technique that is often used in daily dental and surgical treatment. However, the failure rate reaches 15-20% because many factors affect the technique's success. Therefore, this descriptive study aims to determine the knowledge of clinical dental students regarding the inferior alveolar nerve block technique and the management of the failure associated with its characteristics. A cross-sectional approach was employed by using a validated questionnaire consisting of 2 parts, namely 6 general questions and 12 knowledge questions, which were distributed to 68 clinical dental students in the Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas Sumatera Utara in 2019. The results showed that 51.5% of the students had good knowledge, 41.2% had fair knowledge and 7.4% had less knowledge. The highest percentage of students based on male gender had fair knowledge (10 people out of 15) and the female had good knowledge (30 people out of 53). The clinical dental students’ level of knowledge based on whether they have ever or never failed to perform an anesthetic block technique is in a good category. In conclusion, most of the clinical dental students at the Department of Oral Surgery in 2019 had a good level of knowledge about the inferior alveolar nerve block technique and its failure management.